2015
DOI: 10.1021/acsami.5b03879
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Collagen Scaffold Neutralizing the Myelin-Inhibitory Molecules Promoted Neurites Outgrowth in Vitro and Facilitated Spinal Cord Regeneration in Vivo

Abstract: Research has demonstrated that many myelin-associated inhibitory molecules jointly contribute to the failure of adult spinal cord regeneration. Therapies comprehensively targeting the multiple inhibitory nature of the injured spinal cord are being concerned. Here, two collagen-binding proteins, CBD-EphA4LBD and CBD-PlexinB1LBD, were constructed, respectively, to neutralize the axon guidance molecules ephrinB3 and sema4D that inhibit the regeneration of nerve fibers. The two neutralizing proteins have proven th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 34 publications
3
47
0
Order By: Relevance
“…The NeuroRegen scaffold bridges the gap of the lesion and acts as a vehicle to deliver stem cells or biomolecules to promote neural regeneration. In our previous study, a functional biomaterial consisting of NeuroRegen scaffold, biologically active molecules (neurotrophic factors or antagonists to myelin-associated inhibitors), and stem cells was developed that greatly promoted neural regeneration and functional recovery in SCI animals (Han et al, 2010;Han et al, 2015;Li et al, 2015;Li et al, 2013). In future work, biologically active molecules or stem cells could be added to the NeuroRegen scaffold for clinical SCI repair.…”
Section: Discussionmentioning
confidence: 99%
“…The NeuroRegen scaffold bridges the gap of the lesion and acts as a vehicle to deliver stem cells or biomolecules to promote neural regeneration. In our previous study, a functional biomaterial consisting of NeuroRegen scaffold, biologically active molecules (neurotrophic factors or antagonists to myelin-associated inhibitors), and stem cells was developed that greatly promoted neural regeneration and functional recovery in SCI animals (Han et al, 2010;Han et al, 2015;Li et al, 2015;Li et al, 2013). In future work, biologically active molecules or stem cells could be added to the NeuroRegen scaffold for clinical SCI repair.…”
Section: Discussionmentioning
confidence: 99%
“…CBD is a heptapeptide (TKKTLRT) derived from collagenase and can specifically bind to collagen I (de Souza & Brentani, ). CBD‐fused proteins have been expressed to bind collagen scaffolds to facilitate spinal cord regeneration and to bind to collagen gel to recruit endogenous stem cells for myocardial infarction treatment (Li et al, ; Sun et al, ). The immunoblotting assay proved the high expression levels of collagen I and other main ECM components such as fibronectin and laminin in liquid ECM we prepared.…”
Section: Discussionmentioning
confidence: 99%
“…A CBD derived from collagenase was used for enhancing the binding ability of EGFR‐Fab with collagen scaffold. In the past several years, multiple growth factors were fused with CBD to achieve controlled release from collagen scaffold . Our previous study also demonstrated that CBD‐EGFR‐Fab increased the binding ability with collagen for target cancer therapy .…”
Section: Discussionmentioning
confidence: 99%